Penyuluhan Hukum Peran Sekolah Dalam Pencegahan Pernikahan Anak di Bawah Umur - Fransiska Novita Eleanora; Zulkifli Ismail; Melanie Pita Lestari (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2022)
This community service activity can provide knowledge and understanding to schools, especially teachers as educators of students to be able to provide understanding, knowledge and understanding to always be introspective as not to fall into marriage a young age where one way is to avoid association free, which will have an impact on unwanted pregnancies in adolescents so that they do not fall into marriage at a young age which can later harm themselves. Where in addition existence of free association, it is also due to general factors. Besides that, teachers have the right to provide protection and prevention from underage marriages, because children are not yet unstable in their mental maturity and mental maturity, so they need supervision and guidance not only from other people. only parents but also teachers as a place for students and students to knowledge and learn and the implementation of this service activity in order to knowledge and understanding in preventing underage marriages providing socialization to students, that if you marry at a young will harm yourself because can no longer receive education and health aspects will damage women's reproduction. The activity carried through the zoom application with presentation of material by resource persons and followed by a question and answer session with participants, legal counseling so that understanding and impact consequences of child marriage could be known, so it necessary to provide legal counseling to teachers and students. so that understanding based on legal basis, namely the law child protection, and implementation of this counseling must always be improved by prioritizing protection for children that fall into underage marriage. This activity can be followed up carrying out this legal counseling between schools to increase knowledge and understanding of the factors and impacts of underage marriage.